1985
DOI: 10.1111/j.1432-1033.1985.tb08839.x
|View full text |Cite
|
Sign up to set email alerts
|

Localization of the sites of ADP‐ribosylation and GTP binding in the eukaryotic elongation factor EF‐2

Abstract: Tryptic cleavage of EF-2, molecular mass 93 kDa, produced an 82-kDa polypeptide and a 10-kDa fragment, which was further degraded. By a slower reaction the 82-kDa polypeptide was gradually split into a 48-kDa and a 34-kDa fragment. Similarly, treatment with chymotrypsin resulted in the formation of an 82-kDa polypeptide and a small fragment. In contrast to the tryptic 82-kDa polypeptide the corresponding chymotryptic cleavage product was relatively resistant to further attack. The degradation of the 82-kDa pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
24
1

Year Published

1986
1986
2012
2012

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 38 publications
0
24
1
Order By: Relevance
“…Therefore, the toxin is able to bind eEF-2-GTP as it approaches the ribosome before forming the pre-translocation complex, as well as after it has departed the ribosome once GTP has been hydrolyzed. Earlier work using autoradiography had suggested that when NAD ϩ and diphtheria toxin (a catalytically similar toxin to ETA) is added to GTP-bound eEF-2, the factor is not ribosylated (32). However, the present work showed that the presence of bound guanyl nucleotides to eEF-2 did not alter the enzyme reaction rate compared with native eEF-2 (Table III).…”
contrasting
confidence: 53%
“…Therefore, the toxin is able to bind eEF-2-GTP as it approaches the ribosome before forming the pre-translocation complex, as well as after it has departed the ribosome once GTP has been hydrolyzed. Earlier work using autoradiography had suggested that when NAD ϩ and diphtheria toxin (a catalytically similar toxin to ETA) is added to GTP-bound eEF-2, the factor is not ribosylated (32). However, the present work showed that the presence of bound guanyl nucleotides to eEF-2 did not alter the enzyme reaction rate compared with native eEF-2 (Table III).…”
contrasting
confidence: 53%
“…The generated fragments were separated on SDS/polyacrylamide gradient gels containing 10-20% (w/v) acrylamide [4] and transferred to glassfiber filters as above. The stained filters were exposed to autoradiography for 3 weeks at -8O"C, and the fragmentation products were sequenced as above.…”
Section: Chemicalsmentioning
confidence: 99%
“…Oxidized GTP (oGTP) has been used as a reactive GTP analogue for affinity labelling of the GTP-binding domain of translational factors [4,131. The reagent contains two reactive aldehyde groups in the ribose ring, capable of reacting with neighbouring amino groups [14].…”
mentioning
confidence: 99%
“…It appears to be more likely that eubacterial EF-G is not modified by the action of diphtheria toxin, because the histidine residue at position 735 and its surrounding sequence is not present in the sequence of EF-G and shows no significant similarity to EF-2. ADP ribosylation of EF-2 reduces its affinity for the ribosome, leading to inhibition of protein synthesis [19]. lherefore, the carboxyl-terminal half is considered to contain the domain involved in the interaction of EF-2 with the ribosome and toxin.…”
Section: Protein Sequence Comparisonmentioning
confidence: 99%